2008
DOI: 10.1002/cne.21827
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of the cristae ampullares in the squirrel monkey (Saimiri sciureus)

Abstract: Type I hair cells outnumber type II hair cells (HCs) in squirrel monkey (Saimiri sciureus) cristae by a nearly 3:1 ratio. Associated with this type I HC preponderance, calyx fibers make up a much larger fraction of the afferent innervation than in rodents . To study how this affected synaptic architecture, we used disector methods to estimate various features associated with type I and type II HCs in central (CZ) and peripheral (PZ) zones of monkey cristae. Each type I HC makes, on average, 5-10 ribbon synapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 81 publications
(209 reference statements)
2
47
0
Order By: Relevance
“…Ultrastructural data will be necessary to resolve this and to determine whether, in fact, the spines form synaptic contacts. Interestingly, spines appear to contact hair cells well above the basolateral region where synaptic ribbons are found (Lysakowski and Goldberg 2008;Wersäll 1954;review: Eatock and Lysakowski 2006). Preliminary data using an antibody against CtBP2 as a synaptic ribbon marker suggest that at least some spine-hair cell contacts involve no synaptic ribbons (Peterson EH, unpublished observation).…”
Section: Six Classes Of Utricular Afferents Have Distinctive Morpholomentioning
confidence: 99%
“…Ultrastructural data will be necessary to resolve this and to determine whether, in fact, the spines form synaptic contacts. Interestingly, spines appear to contact hair cells well above the basolateral region where synaptic ribbons are found (Lysakowski and Goldberg 2008;Wersäll 1954;review: Eatock and Lysakowski 2006). Preliminary data using an antibody against CtBP2 as a synaptic ribbon marker suggest that at least some spine-hair cell contacts involve no synaptic ribbons (Peterson EH, unpublished observation).…”
Section: Six Classes Of Utricular Afferents Have Distinctive Morpholomentioning
confidence: 99%
“…In mammals ( Figures 1A,B ), the efferent vestibular system (EVS) begins as hundreds of parent neurons in the dorsal brainstem, which project bilaterally and then branch extensively to make numerous synapses on type II hair cells and afferent terminals including calyces surrounding type I hair cells (Lysakowski et al, 1995; Holt et al, 2006; Lysakowski and Goldberg, 2008). At these synapses, CGRP is commonly colocalized in presynaptic efferent varicosities with choline acetyltransferase (ChAT), the enzyme that catalyzes the synthesis of acetylcholine (ACh), the predominant EVS transmitter (Goldberg, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows representative images of vestibular neuroepithelia under light microscopy with sufficient morphological detail to distinguish between types I and II hair cells (HCs). Consistent with commonly accepted morphologic criteria (Lysakowski and Goldberg 2008;Merchant 1999;Lyford-Pike et al 2007), type I HCs were identified based on their flask shape and halo-like nerve calyx, whereas type II HCs were cylindrical and lacked a clear nerve chalice. To quantitatively evaluate the distribution of HCs in each vestibular end organ, we adopted methodologies developed by Merchant (Merchant 1999) for quantification of vestibular HCs in horizontally sectioned human temporal bones.…”
Section: Histopathologic Evaluationmentioning
confidence: 67%